An eave-like model for the welding of 304 stainless-steel tailor-welded blanks with different thicknesses. (November 2020) - Zhu, Hongbo; Cheng, Bo; Ma, Guangyi; Lin, Xingchen; Zhang, Yawei; Wu, Dongjiang; Ning, Yongqiang; Wang, Lijun
Highlights: A novel welding model is introduced for the butt welding of tailor-welded blanks. Inspection results prove that this method can satisfy the industrial requirement. It can simplify processing procedures and improve production efficiency. Abstract: Due to its excellent corrosion resistance and machinability, stainless-steel material has been widely used in many different areas, such as nuclear power and the aircraft industry. In these applications, the stainless-steel parts often consist of tailor-welded blanks with different thicknesses. It is crucial to keep the tailor-welded blanks of high quality in order to satisfy the demanding requirements. To make the welding process of tailor-welded blanks simple and efficient, a novel welding model for the eave-like structure is proposed in this paper. Based on this model, the butt welding of tailor-welded blanks with a plate thickness combination of 2.0 mm and 1.0 mm are successfully completed by high power diode laser sources. For further inspecting the performance of the welded bead, we analyze the microstructure and evaluate the mechanical strength. The results prove that our tailor-welded blanks can satisfy the industrial requirements. This work gives an experimental guide on the welding of tailor-welded blanks with different thicknesses.